Multi-dimensional evaluation of power market based on multiple attribute decision making. (August 2022) - Cui, Jinrui; Li, Yating; Lin, Zhemin; He, Chuan; Wang, Pei; Li, Yongbo; Liu, Xinyi; Zhang, Zhi; Qian, Hanhan; Lin, Zhenzhi; Yang, Li
Abstract: Power market evaluation can reflect the problems in market construction and operation, which is of great significance to the healthy development of power market and the improvement of market rules. Nowadays, several countries are still in the progress of power market liberalization, and an effective power market evaluation system has not been established. In this paper, a hierarchical evaluation system of power market is established according to the construction situation of the developing power markets, which includes market competition level, market operation level, market development level, market opening level and market efficiency level. Then, the Delphi method and the entropy method are used to comprehensively weight the index based on the multiple attribute decision-making theory, and radar charts are used to evaluate the power market. By using the proposed evaluation index and method, the operation condition of a provincial power market in China is analyzed.